Building Late-Life Resilience to Prevent Elder Abuse: A Randomized Controlled Pilot Study of the EMPOWER Program, Arizona, 2019-2021 - Yahner, Jennifer ([Verlag nicht ermittelbar], 2023)
Over the past two decades, as the proportion of older Americans has increased, so too have instances of elder abuse, including physical, emotional, and sexual abuse; financial exploitation; and caregiver neglect. The most recent national survey estimates show at least 1 in 10 community-residing older adults experience elder abuse each year, which translates to over 7 million Americans annually. Rates of abuse are magnified for older adults with the least financial and social resources, including those with low incomes, living in isolated rural communities, and facing structural barriers such as systemic racism. Emerging research on the COVID-19 pandemic prompts even greater concern for elder abuse: the virus has disproportionately affected older adults, resulting in increased social isolation, physical health impairment, and exposure to COVID-related fraud. Recognizing the urgent need to develop and rigorously evaluate programs aimed at preventing elder abuse, the US Department of Justice's National Institute of Justice funded a demonstration from 2017 to 2021 during which researchers from the Urban Institute and practitioners at the Phoenix-based Area Agency on Aging, Region One ("the Area Agency") co-developed an elder abuse prevention program in Maricopa County, Arizona, which Urban's team then evaluated through a randomized controlled pilot study. This multiphase demonstration included an initial planning phase and a subsequent pilot study, which is the focus of this report. The EMPOWER: Building Late-Life Resilience program is a 12-week in-home intervention, with one-hour weekly visits designed to empower community-residing older adults with the resiliency and resources to lead safe and healthy lives throughout the aging process. EMPOWER provides one-on-one assessments, client-centered prevention education, and needs-responsive life skills training embedded in a series of cognitive reframing conversations with an experienced facilitator. The program has eight modules, each of which culminates in an action plan focused on strengthening a client's internal assets and identifying sources of positive social support. Caseworkers facilitate motivational discussions centered on clients' self-identified goals and action planning, with the aim of optimizing clients' home safety, physical health, social connectedness, and emotional and financial well-being.